Sử dụng quy trình 4C trong dạy học chủ đề “Hình học trực quan” (Toán 9) theo định hướng giáo dục STEM - Phạm, Thị Hồng Hạnh; Nguyễn, Vũ Thảo Vân; Nguyễn, Mai Hương; Lương, Thùy Dương (Tạp chí Giáo dục, 2025)
STEM education was introduced to meet the need for developing high-quality human resources in the digital age. This model emphasizes learning through practice, developing critical thinking and problem-solving skills. STEM helps students approach knowledge in an interdisciplinary way, connecting theory with practice. The Ministry of Education and Training has guided the organization of STEM education in high schools through formal teaching and educational activities in schools. The study presents the 4C process in teaching the topic “Visual Geometry” (Math 9) with the STEM education approach and illustrates this process in teaching the STEM topic “Creating a simple handheld vacuum cleaner” to stimulate students’ interest in learning, promote creativity, critical thinking, problem-solving skills in practice and nurture future career dreams. The 4C process has been used as a teaching strategy to promote the integration of subjects and develop comprehensive competencies for students, helping them to apply multidisciplinary knowledge to solve practical problems related to mathematical knowledge.